2001
DOI: 10.1007/s004390100465
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic effects of balanced X-autosome translocations in females: a retrospective survey of 104 cases reported from UK laboratories

Abstract: Females with balanced X-autosome translocations are a clinically heterogeneous group of patients in which X breakpoint position and replication behaviour may influence phenotypic outcome. This study reviewed all cases reported by UK cytogenetics laboratories over a 15-year period (1983-1997). Publication bias was avoided by reviewing all reported cases. One hundred and four female carriers were identified, 62 of who were probands. By reason for referral, these were: multiple congenital abnormalities and/or dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 34 publications
2
38
0
1
Order By: Relevance
“…This can lead to the expression of X-linked recessive disorders in heterozygous women if the derivative X-chromosome harbours a recessive disease allele or if the translocation disrupts a disease causing gene. 19 We have determined by standard cytogenetic analyses that the most extremely skewed girl (III.9) has a normal karyotype (data not shown), and by tiling path array CGH (SMRT v2) at submegabase resolution that no amplifications or deletions are present (data not shown). Thus, the dramatically skewed XCIRs in this family are unlikely to be due to chromosomal abnormalities.…”
Section: Resultsmentioning
confidence: 99%
“…This can lead to the expression of X-linked recessive disorders in heterozygous women if the derivative X-chromosome harbours a recessive disease allele or if the translocation disrupts a disease causing gene. 19 We have determined by standard cytogenetic analyses that the most extremely skewed girl (III.9) has a normal karyotype (data not shown), and by tiling path array CGH (SMRT v2) at submegabase resolution that no amplifications or deletions are present (data not shown). Thus, the dramatically skewed XCIRs in this family are unlikely to be due to chromosomal abnormalities.…”
Section: Resultsmentioning
confidence: 99%
“…However, infertility because of gonadal dysgenesis is not uncommon among women with a breakpoint in the critical region Xq13 → q27 (a narrow region within Xq22 is not critical, Therman et al, 1990). In a UK collaborative study of 104 females with X-autosome translocations Waters et al (2001) described the phenotype in about one-third of all carriers with early age of menopause (before the age of 40) through to primary amenorrhea. Therapy of sterility because of manifested premature ovarian failure is difficult.…”
Section: X-autosome Translocation In the Femalementioning
confidence: 99%
“…In a report of a 104 cases from the UK, Waters et al found in the majority of the cases the normal X-chromosome was preferentially inactivated, supporting the concept that either functional autosomal monosomy or X disomy may give rise to an abnormal phenotype and therefore is naturally avoided [13].…”
Section: Discussionmentioning
confidence: 85%